KELEMAHAN MATERIAL: ANALISIS ATAS UKURAN PEMERINTAHAN DAN BELANJA MODAL SERTA DAMPAKNYA TERHADAP OPINI AUDITOR (Studi Pada Kabupaten/ Kota Se-Jawa Tengah) - Damayanti, Theresia Woro; Sari, Poppy Septia (Jurnal Manajemen dan Keuangan, 2011)
Good Governance signed with the three main pillars which become the basic element that interlocked with others. The three basic elements are participation, transparency, and accountability. Because of that, the region government has to own an internal controlling system which can form and realize a good governance. In this condition, the total of region income and capital expenditure which become a tool in cotrolling the regionâs financial become a big role in forming and realizing the good governance. Moreover, the aim of this research is that to analyze whether there is a significance influence between the government size and capital expenditure towards the auditorâs opinion in the regent and city in the Central Java Province. This research used 29 regents and 6 cities in the Central Java Province as the sample. The operational data of the variable used the material weakness of internal controlling system and the characteristics of the region government which measured with the total of the regionâs income and the proportion of capital expenditure toward the total regionâs charges also auditorâs opinion. Moreover, the researchâs analysis used statistic analysis in descriptive quatitative and inferential statistic using double regrecy analysis and logistic. The result this research proved that there is no significance influence between the governmentâs size and capital expenditure toward the material of internal controlling systemâs weakness also there is no significance influence between internal controlling systemâs weakness toward the auditorâs opinion.Keywords : The materialâs weakness, governmentâs size, capital expenditures and auditorâs opinion.]